Reaffirming legal ethics : taking stock and new ideas - International Legal Ethics Conference 2008 : Gold Coast, Qld.); Tranter, Kieran; Griffith University. Law School; University of Queensland. Law School (London : Routledge, 2010)
'This book, the first of three, arises out of papers delievered at the Third International Legal Ethics Conference held at the Gold Coast, Queensland, Australia in July 2008. The conference was hosted jointly by Griffith Law School at Griffith University and the T.C. Beirne School of Law at The University of Queensland.'--P. vii.
Introduction / Kieran Tranter ... [et al.] -- The philosophical foundations of legal ethics : a roundtable / Christine Parker -- Personal integrity and professional ethics / Deborah L. Rhode -- Legal advising and the rule of law / W. Bradley Wendel -- Tales of terror : lessons for lawyers from the'War on Terrorism' / David Luban -- Legal ethics in a post-westphalian world : building the international rule of law and other tasks / Charles Sampford -- An opportunity for the ethical maturation of the law firm : the ethical implications of incorporated and listed law firms / Christine Parker -- Carnegie's missing step : prescribing lawyer retraining / Lawrence K. Hellman -- Professionalism and pro bono publico / Lorne Sossin -- The psychology of good character : the past, present and future of good character regulation in Canada / Alice Woolley and Jocelyn Stacey -- The'self-regulation' misnomer / Fred C. Zacharias -- Why good intentions are often not enough : the potential for ethical blindness in legal decision-making / Kath Hall.
Includes bibliographical references and index.
Keywords: Legal ethics -- Congresses